Freemium Business Models as the Foundation for Growing an E-business Venture: A Multiple Case Study of Industry Leaders - Franziska Günzel-Jensen; Anna B. Holm (Journal of Entrepreneurship, Management and Innovation)

(untitled)
In e-business freemium business models have become legitiate. However, current research provides litte insight on how the free and premium offring should be employed to lead to growth and success in the long run. The presented research aims to fil this gap by investiatig how the property ‘free’ was employed in young entrepreneurial ventures’ business models in the initil life-cycle stages – opportunity recognitin, market entry, and market exploitatin. We fid that various forms of freemium business models are employed through the initil life-cycle stages of a new venture for reasons of trial-and-error, learning, exploratin, legitiizatin and resource acquisitin. A freemium business model can also serve as a nascent business model, though without a sustainable monetiatin component, for fiding a sustainable business model through a series of dynamic adjustments. With our fidings we contribute to the business model literature in three ways: First, our empirical fidings show the many-sidedness of the component ‘free’ in freemium business models. Free users are of importance for network building, exploratin and exploitatin and growth over tie. Moreover, free users enable directly and indirectly further resource acquisitin. Second, while previous literature has taken a stati perspectie, we contribute by illustratig the dynamic process of strategic business model design for growth. Finally, we introduce the concept of the nascent business model which is new to the literature.